2013
DOI: 10.1111/acem.12137
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Observational Study of the Development of Progressive Organ Dysfunction and Therapeutic Interventions in Normotensive Sepsis Patients in the Emergency Department

Abstract: Objectives: Progressive organ dysfunction is the leading cause of sepsis-associated mortality; however, its incidence and management are incompletely understood. Sepsis patients with moderately impaired perfusion (serum lactate 2.0 to 3.9 mmol/L) who are not in hemodynamic shock ("preshock" sepsis patients) may be at increased risk for progressive organ dysfunction and increased mortality. The objectives of this study were to: 1) quantify the occurrence of progressive organ dysfunction among preshock sepsis pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
5
26
1
Order By: Relevance
“…In addition, Kennedy et al (4) found a nonsignificant trend of increased bands more than 5% in patients with sepsis requiring transfer to the ICU within 4 hours, and in our study, we found that bandemia (> 10%) was associated with progression from sepsis to septic shock (3,17). Arnold et al (18) found only the initial level of organ dysfunction as measured by a modified Sequential Organ Failure Assessment score was associated with progressive organ dysfunction in a multicenter cohort of preshock sepsis patients. Gender, initial individual physiologic variables including serum lactate, and comorbidities were not associated with progressive organ dysfunction (3).…”
Section: Discussionsupporting
confidence: 68%
“…In addition, Kennedy et al (4) found a nonsignificant trend of increased bands more than 5% in patients with sepsis requiring transfer to the ICU within 4 hours, and in our study, we found that bandemia (> 10%) was associated with progression from sepsis to septic shock (3,17). Arnold et al (18) found only the initial level of organ dysfunction as measured by a modified Sequential Organ Failure Assessment score was associated with progressive organ dysfunction in a multicenter cohort of preshock sepsis patients. Gender, initial individual physiologic variables including serum lactate, and comorbidities were not associated with progressive organ dysfunction (3).…”
Section: Discussionsupporting
confidence: 68%
“…A handful of smaller studies evaluated patients with sepsis with intermediate lactate values and reported similar findings (15,16,18,(28)(29)(30). In our large, modern cohort, we confirm that rising index lactate values were associated with increased mortality.…”
Section: Discussionsupporting
confidence: 84%
“…We believe that this is an important consideration that should be addressed by future prospective study. Finally, this study did not address clinical changes after index lactate values (e.g., incident hypotension or organ failure) that might have altered lactate values or fluid administration practice independently of our observed variables (14,18,29,41).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the number of SIRS criteria and the thresholds for laboratory values such as serum lactate, these systems have a wide range of sensitivity and false positives [45,46]. Implementation of these early warning systems in various hospital settings has led to improved outcomes, including decreased time to antibiotic administration [47] and less progression to multi-organ failure [48]. For infants and children, the Pediatric Early Warning System (PEWS) was developed as a tool for bedside caregivers to assess cardiorespiratory and neurologic deterioration but its impact on sepsis-related outcomes has not been tested [49].…”
Section: Alert Systems and Rapid Response Teamsmentioning
confidence: 99%